In Situ Measurement of Nitrate Flux and Attenuation Using a Soil Passive Flux Meter. Issue 3 (1st May 2019) - Desormeaux, Amanda; Annable, Michael D.; Dobberfuhl, Dean; Jawitz, James W.
Abstract : This work enhances our understanding of catchment‐scale N budgets by demonstrating the modification and application of a simple method for direct in situ measurements of vadose zone nitrate leaching and attenuation. We developed a soil passive flux meter (SPFM) to measure solute leaching based on a modified design of ion‐exchange resin columns, and we tested the design in numerical simulations, laboratory experiments, plot‐scale field experiments, and a catchment‐scale field deployment. Our design minimized flow divergence around the resin column to attain nearly 100% capture of surface applied tracers in plot‐ and catchment‐scale deployments. We found that mixing resin with native soil and extending the column height 10 cm above the resin layer minimized divergence of soil water around the column, resulting in a field‐measured convergence factor (χ) of 1.3 that was consistent with numerical simulations. For catchment‐scale testing, SPFMs were used at nine sites in three dominant land uses (crop, pasture, and turf) with known N inputs in two deployments, one during the 4‐mo wet season and an additional set during the 8‐mo dry season, to obtain integral annual measures of soil nitrate fluxes. In situ measured nitrate leaching determined from the SPFMs was positively correlated with known N inputs ( R 2 = 0.55, p < 0.05) and attenuation averaged 67% (± 24% SD) of inputs across all sites. Although N inputs explain a large portion of the variability, our results emphasize the importance of both inter‐ and intra‐land use variability in landscape‐scale N budgets. Core Ideas: We developed a soil passive flux meter (SPFM) to measure solute leaching in situ. Our design minimized flow divergence around the resin column (nearly 100% capture). The SPFMs provided robust and accurate measurements of soil nitrate leaching. The SPFMs, together with N input data, enabled assessment of nitrate attenuation.